Clinical prevalence of diseases and disorders of cattle at the Upazilla Veterinary Hospital, Chauhali, Sirajganj (Research in Agriculture Livestock and Fisheries, 2015)
An investigation was undertaken to determine the general clinical prevalence of diseases and disorders in cattle at the Upazilla Veterinary Hospital, Chauhali, Sirajganj during the period from January to December 2014. A total of 2646 clinical cases on cattle were recorded and analyzed. Diagnosis of each of the clinical cases was made on the basis of owner history, clinical examination and common laboratory techniques. The clinical cases were divided into three groups on the basis of treatment required viz. (1) Medicinal (2) Gynaeco-obstetrical and (3) Surgical cases. Among the three types of cases, medicinal cases constituted the highest percentage (79.33%) in comparison to gynaeco-obstetrical (11.60%) and surgical (9.07%) cases. Among the medicinal cases, the highest cases was recorded with parasitic diseases (55.97%), followed by infectious diseases (24.21%) and digestive disorders (10.34%). Other cases were general systemic states (3.91%), musculo-skeletal disorder (1.57%), skin condition (1.57%), metabolic diseases (1%), respiratory disorders (0.76%), sensory organ diseases (0.43%) and dog biting (0.24%). Among the gynaecoobstetrical cases, repeat breeding (42.35%), anestrous (31.60%), orchitis (9.77%), posthitis (5.86%), dystocia (4.89%) and retained placenta (4.23%) were recorded as major gynaecoobstetrical problems in cattle. Navel-ill (45%), myiasis (43.33%), abscess (6.25%) and fracture (3.34%) were recognized as the main disorders which required surgical interventions. Prevalence of diseases was high (39.38%) in summer season (March-June) followed by (34.73%) in winter (November-February) and lowest (25.89%) in rainy season (July-October). It may be concluded that a number of diseases with various percentages have been occurring in the Chauhali upazila and this report may help to develop control strategies against major diseases reported in this study.Res. Agric., Livest. Fish.2(3): 465-474, December 2015